The Experience of the Master Classes as a Means of Formation of Readiness of Teachers to Implement Innovation - Kushnir, Nataliya; Osipova, Nataliya; Valko, Nataliya; Litvinenko, Olena (Information and Communication Technologies in Education, Research, and Industrial Applications, 2017)
The article describes the experience of the master classes for school teachers and university lecturers to use ICT in the educational process. Improving teacher’s/lecturer’s qualification involves their willingness to follow the advanced technology. However, there are several factors that should be considered in the preparation of training courses for teachers. The authors consider the technology of the master classes as an alternative to long-term courses. This approach has several advantages: short term, productivity at work. During the master-class the main goal is not to teach how to use the technology perfectly but to show its advantages, persuade to use a particular technology, demonstrate the ease of use, and motivate teachers for the further use of the offered technologies in their professional activity. The experience of master classes for teachers of Kherson and Kherson region over the past 5 years was analyzed.